Effectiveness of a five-level Paediatric Triage System: an analysis of resource utilisation in the emergency department in Taiwan. Issue 9 (14th September 2012) - Chang, Yu-Che; Ng, Chip-Jin; Wu, Chang-Teng; Chen, Li-Chin; Chen, Jih-Chang; Hsu, Kuang-Hung
Abstract : Objectives: To examine the effectiveness of a five-level Paediatric Triage and Acuity System (Ped-TTAS) by comparing the reliability of patient prioritisation and resource utilisation with the four-level Paediatric Taiwan Triage System (Ped-TTS) among non-trauma paediatric patients in the emergency department (ED). Methods: The study design used was a retrospective longitudinal analysis based on medical chart review and a computer database. Except for a shorter list of complaints and some abnormal vital sign criteria modifications, the structure and triage process for applying Ped-TTAS was similar to that of the Paediatric Canadian Emergency Triage and Acuity Scale. Non-trauma paediatric patients presenting to the ED were triaged by well-trained triage nurses using the four-level Ped-TTS in 2008 and five-level Ped-TTAS in 2010. Hospitalisation rates and medical resource utilisation were analysed by acuity levels between the contrasting study groups. Results: There was a significant difference in patient prioritisation between the four-level Ped-TTS and five-level Ped-TTAS. Improved differentiation was observed with the five-level Ped-TTAS in predicting hospitalisation rates and medical costs. Conclusions: The five-level Ped-TTAS is better able to discriminate paediatric patients by triage acuity in the ED and is also more precise in predicting resource utilisation. The introduction of a more accurate acuity and triage system for use in paediatric emergency care should provide greater patient safety and more timely utilisation of appropriate ED resources.